Aṡaru Ṣiyaghi al Asmā’i li Ma’ānihā fī Syi’ri ‘Aqīdati al Muslimi li al Syaikhi Mullā ‘Imrān (Dirāsatun Taḥlīliyyatun fī ‘Ilmi al Naḥwi) - Nurhidayati, Ade; Nurlaily, NurLaily (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
The purpose of this research is :1) To know the forms of isim in the syair Aqidah Muslim from the side of ta'yin he said. 2) To know the influence of isim forms in terms of ta'yinnya on its meaning in the poem. This research is very useful to look at the influence of isim forms of different points of view as the authors described in this study as a reference as well as to add insight into related things. The type of research used is Pustaka Study. This study can be summed up: 1) Isim contained in syair Aqidah Muslim seen in terms of ta'yinnya is: 1) Ma'rifah:102 words (Dhamir:45, Isim 'Alam:8, Isim Isyaroh:3, Isim Maushul:1, With Alif Lam:32, Ma'rifah because Idhofah:13) and Nakirah: 62. 2) That the forms of Isim in terms of ta'yinnya affect the meaning such as the use of isim ma'rifah to show that a word is devoted to a certain purpose deliberately made by the author to make it easier for the reader to understand the meaning of the word clearly, among them isim dhamir, isim 'alam, isim isyarah, isim maushul ma'rifah with alif lam and mudhof to ma'rifah. While the use of isim nakirah is to indicate that a word is intended with a broad aspect without limitation in understanding the meaning of the word.